ANALYZE THE EFFECT OF THIRD PARTY FUND (TPF), NON-PERFORMING FINANCING (NPF), FINANCING TO DEPOSIT RATIO (FDR) AND PROFIT MARGIN ON MURABAHAH FINANCING OF SHARIA COMMERCIAL BANK - PUTRI SAULA HASNADINA; ADE SOFYAN MULAZID (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2019)
The purpose of this study is to analyze the eﬀect of each variable, Deposits of Third Party Fund (TPF) (X1),Non-Performing Financing (NPF) (X2), Financing to Deposit Ratio (FDR) (X3) and Proﬁt Margin (X4)on Murabahah Financing (Y1). The population of this study was conducted on eleven Sharia CommercialBanks in Indonesia, namely Bank Muamalat, Bank Victoria Syariah, Bank BRI Syariah, Bank BNI Syariah,Bank Syariah Mandiri, Bank Syariah Mega Indonesia, Bank Panin Syariah, Bank Syariah Bukopin, BankBCA Syariah and Bank Maybank Syariah Indonesia. The sample taken was the annual ﬁnancial reportfor ﬁve periods, namely 2011-2015 periods. The analysis technique used panel data regression analysis wastested by F-test and T-test, with a signiﬁcant value of 5%. Based on the results of the T-test and F-test, it canbe known that TPF, FDR and Proﬁt Margin simultaneously have a signiﬁcant positive eﬀect and the NPFpartially have no eﬀect of murabahah ﬁnancing on Sharia Commercial Banks. Adjusted R Square value of0.275352 indicates that the independent variable could give eﬀect the dependent variable of 0.000429%.